Passive Knee Stability After Anterior Cruciate Ligament Reconstruction Using the Endobutton or ToggleLoc With ZipLoop as a Femoral Fixation Device: A Comparison of 1654 Patients From the Danish Knee Ligament Reconstruction Registry. Issue 6 (9th June 2018) - Asmussen, Christian Asmus Peter; Attrup, Mikkel Lindegaard; Thorborg, Kristian; Hölmich, Per
Background: Biomechanical studies show varying results regarding the elongation of adjustable fixation devices. This has led to growing concern over the stability of the ToggleLoc with ZipLoop used in anterior cruciate ligament (ACL) reconstruction (ACLR) in vivo. Purpose/Hypothesis: The purpose of this study was to compare passive knee stability 1 year after ACLR in patients in whom the Endobutton or ToggleLoc with ZipLoop was used for femoral graft fixation. The hypothesis was that the ToggleLoc with ZipLoop would be inferior in knee stability to the Endobutton 1 year after primary ACLR. Study Design: Cohort study; Level of evidence, 2. Methods: Data from 3175 patients (Endobutton: n = 2807; ToggleLoc with ZipLoop: n = 368) were included from the Danish Knee Ligament Reconstruction Registry (DKRR) between June 2010 and September 2013. Data were retrieved from standardized ACL forms filled out by the operating surgeon preoperatively, during surgery, and at a clinical examination 1 year after surgery. Passive knee stability was evaluated using 1 of 2 arthrometers (Rolimeter or KT-1000 arthrometer) and the pivot-shift test. Using the same database, the number of reoperations performed up to 4 years after primary surgery was examined. Results: Full data were available for 1654 patients (Endobutton: n = 1538; ToggleLoc with ZipLoop: n = 116). ACLR with both devices resulted in increased passive knee stability ( P < .001). Patients who received the ToggleLoc with ZipLoop were found to have a better preoperative ( P = .005 ) and postoperative ( P < .001) pivot-shift test result. No statistically significant difference regarding the number of reoperations ( P = .086) or the time to reoperation ( P = .295) was found. Conclusion: Patients who underwent fixation with the ToggleLoc with ZipLoop had improved passive knee stability 1 year after surgery, measured by anterior tibial translation and pivot-shift test results, similar to patients who underwent fixation with the Endobutton. No difference was seen in knee stability or reoperation rates between the 2 devices.